The Diversity of Wild Musa acuminata Originated from Mount Halimun–Salak National Park Based on Morphology and Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4) Resistance Characters - Ahmad Zaelani; Erwin Fajar Hasrianda; Fajarudin Ahmad; Yuyu Suryasari Poerba (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2021)
ndonesia is well-known as a center of diversity of banana in the world. Here, wild Musa acuminata is growth widely in some areas, included Java islands. However, the genetic diversity study of wild banana, especially in Java Island is still limited. In this study, we observed the genetic diversity of wild banana in Mount Halimun-Salak National Park (TNGHS), West Java, Indonesia and studied its resistance to Fusarium oxysporum f.sp. Cubense tropical race 4 (Foc TR4) using molecular markers. The plant materials were collected and phenotyped in some different locations of conservation area TNGHS from 7 to 11 October 2019. Principal Component Analysis (PCA) was calculated to estimate the genetic diversity on eight accessions of wild M. acuminata based on eighteen morphological characters. Moreover, the study of its resistance traits to Foc TR4 was analyzed by using SCAR markers i.e. ScaU1001 and ScaS0901. The most contributed characters on principal component 2 (PC2) was showed on number of fruits with the value of 0.586 and bract apex shape with value of -0.648 on principal component 3 (PC3). For the resistance study, the eight accessions of wild M. acuminata produced specific band of ScaS0901 marker. The knowledge of the genetic diversity and the resistance study of wild M. acuminata in TNGHS would be useful for conservation strategy and bioprospecting of the wild banana in TNGHS.